PEOPLE’S PARTICIPATION OF DEVELOPMENT PLAN IN LOCAL ADMINISTRATIVE ORGANIZATION IN SUPHANBURI PROVINC.: PEOPLE’S PARTICIPATION OF DEVELOPMENT PLAN IN LOCAL ADMINISTRATIVE ORGANIZATION IN SUPHANBURI PROVINC. - อินทร์จันทร์ ธเนศพล (NKRAFA Journal of Humanities and Social Sciences, 2018)
Research "Public Participation in Development Plan of Local Government Organization The purpose of this study was to 1) study the level of public participation in the development process of the local government organization. 2) To study the relationship between factors and people’s participation in the development plan of the local administration organization. 3) To study the factors affecting the people’s participation in the development process of the local administrative organizations. 4) To study the problems and obstacles of people participation in the process of planning the development of local government organizations. And 5) to study ways to encourage people to participate in the development process of the local government organization. Applying the research methodology using mixed quantitative and qualitative methods. The samples used in quantitative research were: 384 people elected from 10 districts, 39 municipalities and 100 sub-district administrative organizations. The samples used in qualitative research were: The people who are the local development committee, the local development committee, the local development committee And the director of monitoring and evaluation of local development plans. Tools used in quantitative research are: The questionnaire was used for qualitative research. The research found that (1) The level of public participation in the development process of the local government organization in Suphanburi province. Overall, the level of participation was low. The most popular measure was participation in the informational level (To Inform), followed by participation in the consultative level (To Consult). Participation in the level of integration. To Collaborate, To Involve, and To Empower. (2) Analyze the relationship between personal factors and people’s participation in the process. Development plan of local government organization in Suphanburi province. The results showed that the internal motivation factors had statistically significant relationship at .05. The analysis of local government organization factors and public participation in the development process of local administrative organizations in Suphanburi province. The results showed that all factors had statistically significant relationship at .01 level and (3) factors affecting people participation in the development process of local government organizations in Suphanburi. Indicators include personal attributes, attitudes, principles, rules of law, moral principles, participatory principles. And the main value. Factors that do not affect or influence the participation of people in the process of developing the plan. There are five indicators of local administration in Suphanburi Province: reward or benefit, reputation or recognition. Mandatory Transparency (4) Problems and obstacles in public participation in the development process of local administrative organizations in Suphanburi province. Personal factors include motivation in organizational factors, including the rule of law, principles of participation. (5) Guidelines for promoting public participation in the development process of local administrative organizations. In Suphanburi Personality factors include enhancing positive attitudes towards participation. Organizational factors include the strengthening of corporate governance practices.